KOMUNIKASI INSTRUKSIONAL INSTRUKTUR PADA PELATIHAN VOLLY BALL DI MTS MIFTAHUL ULUM KEPENUHAN KABUPATEN ROKAN HULU - Sam, Renika Fitri; Awza, Rusmadi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
MTs Miftahul Ulum Kepenuhan is a school that excels in terms of extra-curricular activities in the kecamatan kecamatan, upstream Rokan Regency. There is one extracurricular activity that has the most outstanding achievements compared to other extracurricular activities, namely in the field of volleyball. The achievements of MTs Mifathul Ulum volleyball include winning 2 axioms in the district, becoming a district representative for POPDA, successfully sending 2 students to PPLP Riau, and others. The purpose of this study was to determine the method used, the communication techniques used and the obstacles that occurred during vollyball training.This study used qualitative research methods. The research was conducted at MTs Miftahul Ulum Kepenuhan, Rokan Hulu Regency. The selection of informants was carried out using purposive technique, with the number of informants, namely 11 people. Data collection techniques consist of observation, interviews, and documentation. Meanwhile, the data analysis technique uses descriptive analysis according to Miles & Huberman. The data validity checking technique used in this research is Participation Extension and Triangulation.The results showed that the method used by the instructor when training students was varied, including the command method used by the instructor in providing directions that had to be done and implemented. The training method is used to improve the ability to play volleyball. a demonstration method that requires an instructor to practice directly what he says. The method of discussion and question and answer is a method intended to accommodate questions from students and overcome problems experienced. training method with friends In this method relying on one friend who is more proficient at playing volleyball. Then there are three communication techniques used, namely, persuasive communication techniques, the techniques needed to be able to stimulate the enthusiasm of students in practicing. Instructive techniques that cover the entire volleyball training process. Human relations techniques are intended to create a team approach and cohesiveness. Then there are three types of obstacles, namely obstacles at the source or from the communicator, obstacles to the channel, namely inadequate tools and field conditions and obstacles to the communicants, namely the absorption and catching power of each different student.